PENGARUH LINGKUNGAN KERJA DAN KINERJA KARYAWAN DI CU KELING KUMANG BATU BUIL KABUPATEN MELAWI - Gusnita, Gusnita (Jurnal Ekonomi Integra, 2023)
This research was conducted with the aim of determining the influence of the work environment on employee performance at CU Keling Kumang Batu Buil Branch, Melawi Regency.  The research method used in this study is a quantitative descriptive research method. The data collection techniques and instruments used are divided into two, namely, primary and secondary data. Data analysis techniques use validity tests, reliability tests, simple linear regression analysis and calculation of coefficients of determination. The research variability consists of an independent variable, namely the work environment (X) and a dependent variable, namely employee performance (Y). The population used as a sample (saturated study) amounted to 30 employees The results of the study found that the work environment (X) that occurred had a significant influence on the performance of employees (Y) in CU Keling Kumang Batu Buil Branch, Melawi Regency.